The Influence of Water Content on the Settlement Behaviour of Polypropylene Fibre-Reinforced Dredged Marine Soil (DMS) - Z. Rosman, M.; Chan, C-M. (International Journal of Engineering and Technology, 2019)
The use of fiber as soil reinforcement is not new in civil engineering field. In the earlier times, rice straw was mixed together with mud or clay to produce construction materials such as brick and concrete. Conventional concrete mix without fiber tends to exhibit brittleness behaviour. Hence, there is a growing attention on using current reinforcement materials such as steel, polypropylene and glass fibers. It is reported that fiber in concrete provide bridging effect, which transfer and distribute load evenly, thus increasing ductility. Now, similar concept of fiber inclusion in concrete can be applied to the case of problematic soil. The addition of chemical additives such as cement in soil resulted with stiffness and brittleness. As solution, numerous studies have shown that the fiber inclusion in soil have increased strength, permeability and ductility. Due to the many studies of fibre-reinforced soil related to its shear strength, the present study will investigate the compressibility behaviour of the fibre-reinforced soil through oedometer test. In this study, the dredged marine soil (DMS) was mixed together with 0.25, 0.5, 0.75 and 1 % of polypropylene (PP) fiber. Two conditions of soil, namely high water content (1.40LL) and low water content (0.90LL) were tested. Samples with 0.90LL water content show great reduction of settlement than samples with 1.40LL water content. The outcome of this study will suggest the beneficial reuse of DMS for engineering application such as backfill material, land reclamation or clay liner for landfills.Â Â